1998
DOI: 10.1038/sj.bmt.1701308
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood CD34+ cell count reliably predicts autograft yield

Abstract: Summary:A reliable measure to predict peripheral blood progenitor cell (PBPC) autograft CD34 + cell content is required to optimize the timing of PBPC collection. We prospectively examined the peripheral blood (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
36
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 9 publications
6
36
1
Order By: Relevance
“…Subsequently, it has been shown that mononuclear cell counts correlate poorly with CD34 þ cells; hence, the true number of infused stem cells in early studies is not well known. 18,19 At the time of earlier studies, fluoroquinolone antibiotic prophylaxis was not available. Ciprofloxacin was not approved until 1987, and triazole antifungal antibiotics, such as ketoconazole and fluconazole, were not introduced until 1990.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it has been shown that mononuclear cell counts correlate poorly with CD34 þ cells; hence, the true number of infused stem cells in early studies is not well known. 18,19 At the time of earlier studies, fluoroquinolone antibiotic prophylaxis was not available. Ciprofloxacin was not approved until 1987, and triazole antifungal antibiotics, such as ketoconazole and fluconazole, were not introduced until 1990.…”
Section: Discussionmentioning
confidence: 99%
“…Each send-out, from Spring 1996 to Autumn 2004 was chronologically assigned with a unique number (i.e., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In this way, we analyzed any effect of the EQA program on the results of the participants as a function of time.…”
Section: Data Processing and Parameter Classificationmentioning
confidence: 99%
“…This emphasizes the need for an adequate prediction of engraftment potency of HSCs in patients after receiving myeloablative therapy followed by HSC transplantation (8)(9)(10)(11). Furthermore, enumeration of CD34þ cells has been shown to be useful in con-siderations of peripheral blood stem cell harvesting (12)(13)(14)(15)(16) and in comparing the efficacy of various PB stem cell mobilization strategies (reviewed by Fruehauf and Kessinger and Sharp) (17,18). Furthermore, CD34þ cell enumeration is useful for monitoring the stem cell yield during graft manipulations, such as immunomagnetic selections, ex vivo expansion, or genetic modifications of HSCs.…”
mentioning
confidence: 99%
“…Flow cytometric enumeration of CD34 þ cells provides a rapid means of measuring this clinically useful surrogate marker of graft adequacy in all sources of HSCs and most transplant centers now determine graft adequacy based on the number of CD34 þ cells/Kg of patient body weight. In addition to determining yield, the number of CD34 þ cells mobilized to the peripheral blood is also a predictor of the success of apheresis (5) and can be used to monitor, ''on-line,'' the yield of CD34 þ cells (6). Although simple flow methods for counting CD34 þ cells date back to the late 1980's (7-13), a standardized multi-parameter protocol that was based on the structural characteristics of the CD34 molecule and the epitopes detected by various CD34 monoclonal antibodies did not emerge until 1994 (14).…”
mentioning
confidence: 99%